Preparation of three-dimensional microstructure vanadium pentoxide positive electrode material based on organic molecule embedding and application of vanadium pentoxide positive electrode material in aqueous zinc ion battery

Synthesis of malonamide intercalated vanadium pentoxide material through hydrothermal method solved the problems of slow reaction kinetics and poor structural stability of vanadium-based materials in aqueous zinc ion batteries, achieving high capacity and long-life battery performance, enhancing the The battery tolerance and cycle stability are achieved.

CN119191349APending Publication Date: 2024-12-27CHANGZHOU UNIV +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411283413.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

There is a lack of high-performance positive electrode materials in aqueous zinc ion batteries, especially vanadium-based materials, which have problems such as slow reaction kinetics, poor electronic conductivity, structural collapse and vanadium dissolution, which affects its electrochemical performance and safety.

Method used

Hydrothermal method is used to synthesize the intercalated vanadium pentoxide material with dendritic structure. By introducing malonamide as an intercalation agent, the layer spacing and active sites of vanadium pentoxide are increased, and the cations and amide anions are weakened. Interactions improve the migration efficiency of zinc ions and inhibit the dissolution of vanadium.

Benefits of technology

The specific capacity, rate capability and cycle stability of vanadium pentoxide are significantly improved, the tolerance and structural stability of the battery are enhanced, and the performance of high-capacity and long-life water-based zinc ion battery is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005042365860000011
    Figure HDA0005042365860000011
  • Figure HDA0005042365860000012
    Figure HDA0005042365860000012
  • Figure HDA0005042365860000021
    Figure HDA0005042365860000021
Patent Text Reader

Abstract

The invention belongs to the field of water-based zinc ion batteries, and particularly relates to a preparation method of a composite positive electrode material with organic molecules embedded into three-dimensional microstructure vanadium pentoxide and application of the composite positive electrode material in the water-based zinc ion batteries. The preparation method comprises the following steps: preparing a large amount of crotch-shaped structure vanadium oxide precursor, adding malonamide into the solution of the vanadium oxide precursor, adjusting the pH value, carrying out hydrothermal treatment, filtering and collecting the precipitate after hydrothermal treatment, washing, drying and calcining to obtain the malonamide intercalation vanadium pentoxide material, and preparing the crotch-shaped structure vanadium pentoxide material by embedding small organic molecules (malonamide). The structural stability and the electric conductivity of the main body material are improved, and the problem of vanadium dissolution caused by water is solved, so that the water-based zinc ion battery with high capacity and long service life is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of aqueous zinc ion batteries, and specifically relates to a preparation method and application of a composite positive electrode material with organic molecules embedded in a three-dimensional microstructure of vanadium pentoxide. Background Art

[0002] One of the challenges facing the practical application of aqueous zinc-ion batteries (AZIBs) is the lack of high-performance cathode materials. 2+ The radius is very small But because Zn 2+ Due to the strong electrostatic effect, it is difficult to find an ideal cathode material. Therefore, most of the literature on AZIBs focuses on the exploration and development of cathode materials. Among them, vanadium-based electrode materials not only have rich valence states, diverse crystal structures and high theoretical capacity, but also can realize multi-electron transfer and help achieve local electrical neutrality, alleviate the polarization problem caused by zinc ion embedding, and thus achieve excellent electrochemical performance. However, it still has disadvantages such as slow reaction kinetics, poor electronic conductivity, structural collapse and vanadium dissolution. In order to solve these problems, many design strategies have been proposed to improve its electrochemical performance, including ion pre-embedding, molecular pre-embedding and introduction of vacancies.

[0003] Guest pre-embedding means that in vanadium pentoxide materials, due to the weak van der Waals force between vanadium oxide layers, under certain conditions, certain ions or molecules can overcome the interlaminar forces in layered vanadium pentoxide and insert into the interlayer gaps of vanadium pentoxide. Usually, the two-dimensional layered material is called the host, and the inserted inorganic ions or organic matter is called the guest. A large number of research results have emerged in the pre-intercalation vanadium oxide with vanadium pentoxide or hydrated vanadium pentoxide as the host and inorganic metal ions and organic matter as guests. For example, CN202311184352.2 A method for preparing an organic small molecule intercalated vanadium pentoxide material and its application. By introducing melamine as an intercalation agent between the vanadium pentoxide layers, the cycle performance of vanadium pentoxide is significantly improved, but because the introduction of the melamine intercalation agent occupies a certain mass, it exhibits a lower specific capacity (280mAh g -1 ). In addition, although the introduction of acetone into vanadium pentoxide enhances its reversibility, the battery's tolerance and structural stability still need to be improved. It explores its application in lithium, magnesium and other batteries, and the electrochemical performance and safety in zinc ion batteries still need further exploration.

[0004] The function of aqueous Zn-ion battery intercalants can also be defined as a “lubricating” effect, where H2O can reduce Zn by solvation. 2+ The effective charge of water molecules on Zn 2+The strong electrostatic interaction between Zn and VO and the solubility of VO often leads to structural damage and slow migration kinetics, which adversely affects the life of VO cathode. Therefore, when performing intercalation reactions, it is necessary to consider that the embedded molecules can enhance the stability between material layers and interact with Zn 2+ Therefore, in the study of vanadium-based materials, the selection and optimization of organic guest molecules are crucial for high-performance ZIBs. Therefore, in the study of vanadium-based materials, the selection and optimization of organic guest molecules are crucial for high-performance ZIBs. Summary of the invention

[0005] The purpose of the present invention is to overcome the defects of the prior art and provide a method for preparing an organic small molecule intercalated vanadium pentoxide material. The present invention synthesizes a dendritic structure of malonamide intercalated vanadium oxide cathode by hydrothermal method. The introduction of intercalation agent makes vanadium pentoxide have larger interlayer spacing and more active sites. The introduction of malonamide can absorb part of the water and effectively inhibit the dissolution of vanadium. Since the interaction between cations and amide anions is weak, this ensures that Zn 2+ The migration efficiency between V2O5 layers. Malonamide intercalated V2O5 exhibits excellent battery performance in terms of specific capacity, rate capability and cycling stability.

[0006] Another object of the present invention is to provide application of the above-mentioned organic small molecule intercalation vanadium pentoxide material in aqueous zinc ion batteries.

[0007] The technical solution of the present invention is as follows:

[0008] The method for preparing the organic small molecule intercalated vanadium pentoxide material of the present invention comprises the following steps:

[0009] (1) The inorganic vanadium source compound and H2C2O4·2H2O are dissolved in deionized water at a molar ratio of 1:3, and stirred vigorously at 80°C for half an hour until a blue transparent solution (VOC2O4) is formed; the obtained VOC2O4 solution is added to a polytetrafluoroethylene container. H2O2 (35wt%) and anhydrous ethanol are slowly added dropwise under stirring. After 20 minutes, the container is sealed in an autoclave and transferred to an oven to react at 160-180°C for 7-9 hours. After natural cooling, the precipitate is collected by centrifugation, washed with water and anhydrous ethanol 3 times, and dried at 60°C overnight to obtain a vanadium oxide precursor. The obtained vanadium oxide precursor is composed of a large number of dendritic structures;

[0010] (2) Adding organic molecules to a dispersion of a vanadium oxide precursor and stirring the dispersion under acidic conditions.

[0011] (3) After vigorous stirring, the orange solution was transferred to a stainless steel autoclave lined with polytetrafluoroethylene, sealed, and maintained at 200°C for 0.5 to 24 hours for hydrothermal treatment. After the hydrothermal treatment, the autoclave was cooled to room temperature, washed with water and ethanol several times, and vacuum dried at 60°C.

[0012] (4) The dried material was further calcined in air at 350 °C for 2 h at a heating rate of 2 °C min -1 , V2O5 with intercalation characteristics is obtained; the final product is denoted as MVO in this article. The product obtained by the above synthesis method without the addition of malonamide is marked as VO.

[0013] Furthermore, the inorganic vanadium source compound in step (1) is selected from at least one of vanadium pentoxide, ammonium vanadate, hydrate of vanadium pentoxide, vanadyl oxalate, vanadyl phosphate, and vanadate. More preferably, vanadium pentoxide is selected as the inorganic vanadium source.

[0014] Furthermore, the inorganic vanadium source compound and oxalic acid in step (1) are stirred with deionized water at a molar ratio of 1:3, and the concentration of the reactant VOC2O4 is 0.66 to 0.165 M. In a preferred embodiment, the concentration of the reactant VOC2O4 is 0.33M.

[0015] Furthermore, in step (2), the molar ratio of the vanadium oxide precursor to the organic small molecule is 1 to 3:0.5 to 1.5. More preferably, the molar ratio of the vanadium oxide precursor to the organic small molecule is 2.5:1.2.

[0016] Furthermore, the pH of the acidic condition can be selected in the range of 1 to 5. More preferably, the reaction is carried out at a pH of 5. When the pH is lower than 5, the structure of the main material is easily destroyed. When hydrochloric acid is not added, the organic molecules cannot be smoothly inserted into the vanadium oxide interlayer.

[0017] Furthermore, the organic molecule is selected from malonamide and malononitrile. Further preferably, the organic molecule intercalation is malonamide. The introduction of malonamide can absorb part of the lattice water, effectively inhibiting the dissolution of vanadium. Since the interaction between the cation and the amide anion is weak, this ensures that Zn 2+ Migration efficiency between V2O5 layers.

[0018] Further preferably, the hydrothermal time in step (3) is 6 hours.

[0019] The organic small molecule intercalated vanadium pentoxide material prepared by the preparation method is used in the positive electrode of zinc ion batteries.

[0020] The innovative features of the present invention are:

[0021] 1. The present invention adopts a simple and easy solvothermal method to synthesize vanadium oxide with adjustable nanostructure by changing the concentration of (VOC2O4) solution. The obtained V2O5 precursor is composed of a large number of tree-like structures. The unique structure has a high theoretical capacity, but its structure is easily degraded during the charge and discharge process. Avoiding the structure from being destroyed leads to unstable cycle life. The present invention selects it as a precursor to prepare malonamide intercalated vanadium pentoxide material. On the basis of the high capacity of inorganic vanadium oxide, the structural stability and conductivity of the main material are improved by embedding organic small molecules (malonamide) to obtain a high-capacity, long-life aqueous zinc ion battery.

[0022] 2. The introduction of malonamide in the present invention can absorb part of the lattice water, effectively inhibiting the dissolution of vanadium. Since the interaction between the cation and the amide anion is weak, this ensures that Zn 2+ Migration efficiency between V2O5 layers.

[0023] 3. The malonamide in the present invention can provide additional active sites and has a certain redox ability, which to some extent makes up for the theoretical capacity of the material reduced due to the intercalation molecules occupying a certain mass. It can also perform a dual storage mechanism, greatly improving the cycle life of vanadium oxide. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is the XRD diagram of the product of Example 1 and Comparative Example 1 in the present invention.

[0025] Figure 2 These are SEM photos of the products obtained in Example 1 and Comparative Example 1 of the present invention.

[0026] Figure 3 1 is a low-magnification SEM photograph of the product obtained by implementing Preparation 1 in the present invention.

[0027] Figure 4 This is a TEM photograph of the product of Example 1 in the present invention.

[0028] Figure 5 It is a zinc storage rate performance diagram of the products of Example 1 and Comparative Example 1 in the present invention.

[0029] Figure 6 The product of Example 1 and Comparative Example 1 of the present invention is 0.5A·g -1 Zinc storage cycle performance diagram under current density.

[0030] Figure 7 It is the XRD diagram of the products of Comparative Example 1 and Comparative Example 2 in the present invention.

[0031] Figure 8 This is a SEM photograph of the product of Comparative Example 2 of the present invention.

[0032] Fig. 9 It is a zinc storage rate performance diagram of the product of Comparative Example 2 in the present invention.

[0033] Fig.10 The product of comparative example 2 in the present invention is 0.5Ag -1 Zinc storage cycle performance diagram under current density.

[0034] Fig.11 The product obtained in Example 2 is at 0.5A·g -1 Zinc storage cycle performance diagram under current density.

[0035] Fig.12 The product obtained in Example 3 was 0.5Ag -1 Zinc storage cycle performance diagram under current density.

[0036] Fig.13 The product obtained in Example 4 was 0.5Ag -1 Zinc storage cycle performance diagram under current density.

[0037] Fig.14 The product obtained in Comparative Example 3 was 0.5Ag -1 Zinc storage cycle performance diagram under current density.

[0038] Fig.15 The product obtained in Example 5 was 0.5Ag -1 Zinc storage cycle performance diagram under current density. DETAILED DESCRIPTION

[0039] The technical solution of the present invention is further illustrated and described below through specific implementation modes in combination with the accompanying drawings.

[0040] Example 1

[0041] (1) Add 1.2 g of V2O5, 40 mL of deionized water, and 2.596 g of oxalic acid dihydrate into a beaker and stir for 30 min until the solution turns blue to obtain a VOC2O4 solution.

[0042] (2) Then, 5 mL of VOC2O4 solution (0.33 M) was added to a 50 mL polytetrafluoroethylene container, and then 1 mL of H2O2 (35 wt%) was added dropwise under stirring. After stirring evenly, 30 mL of ethanol solution was added. Then, the container was sealed in an autoclave and transferred to an electric oven and kept at 170° C. for 8 hours. The reaction material was centrifuged three times with deionized water and anhydrous ethanol, respectively, and dried at 60° C. to obtain the product vanadium oxide precursor (vanadium dioxide).

[0043] (3) 2.5 mmol of vanadium dioxide and 1.2 mmol of malonamide (C3H6N2O2) were dispersed in deionized water, and the pH value was controlled at 5 by hydrochloric acid. After vigorous stirring, the solution was transferred to a stainless steel autoclave lined with polytetrafluoroethylene, sealed and kept at 200°C for 6 hours. After the hydrothermal treatment, the autoclave was cooled to room temperature, washed with water and ethanol three times, and vacuum dried at 60°C.

[0044] (4) The dried material was further calcined in air at 350 °C for 2 h at a heating rate of 2 °C min -1 , and finally the product organic intercalated V2O5 is obtained, which is expressed as MVO.

[0045] Example 2

[0046] The difference between Example 2 and Example 1 is that the 0.33M VOC2O4 solution in step (2) is replaced by a 0.166M VOC2O4 solution, and the other operations are the same as those in Example 1.

[0047] Example 3

[0048] Compared with Example 1, Example 3 differs in that the molar ratio of vanadium oxide precursor to malonamide in step (3) is replaced from 2.5:1.2 to 3:1, and other operations are the same as Example 1.

[0049] Steps (1)-(2) are the same as in Example 1

[0050] (3) 3 mmol of vanadium dioxide and 1 mmol of malonamide (C3H6N2O2) were dispersed in deionized water, and the pH value was controlled at 5 by hydrochloric acid. After vigorous stirring, the orange solution was transferred to a stainless steel autoclave lined with polytetrafluoroethylene, sealed and kept at 200°C for 6 hours. After the hydrothermal treatment, the autoclave was cooled to room temperature, washed with water and ethanol three times, and vacuum dried at 60°C.

[0051] (4) The dried material was further calcined in air at 350 °C for 2 h with a heating rate of 2 °C min-1 to finally obtain the product organic intercalated V2O5.

[0052] Example 4

[0053] Compared with Example 1, Example 4 differs in that malonamide in step (3) is replaced by malononitrile, and other operations are the same as Example 1.

[0054] Example 5

[0055] The difference between Example 5 and Example 1 is that the hydrothermal condition of step (3) "maintaining at 200°C for 6 hours" is replaced by "maintaining at 200°C for 24 hours", and other conditions remain unchanged.

[0056] Comparative Example 1

[0057] The difference between Comparative Example 1 and Example 1 is that the process of adding the organic molecule malonamide (C3H6N2O2) in step (3) is removed, and the other operations are the same as those in Example 1.

[0058] (1) Add 1.2 g of V2O5, 40 mL of deionized water, and 2.596 g of oxalic acid tetrahydrate into beaker a and stir for 30 min until the solution turns blue to obtain solution a, VOC2O4 (0.33 M) solution.

[0059] (2) Then 5 mL of VOC2O4 solution (0.33 M) was added to a 50 mL polytetrafluoroethylene container, and then 1 mL of H2O2 (35 wt%) was added dropwise under stirring. After stirring evenly, 30 mL of ethanol solution was added. Then the container was sealed in an autoclave and transferred to an electric oven and kept at 170° C. for 8 hours. The material obtained by the reaction was centrifuged three times with deionized water and anhydrous ethanol, respectively, and dried at 60° C. to obtain the product vanadium dioxide.

[0060] (3) The vanadium dioxide was further calcined in air at 350 °C for 2 h at a heating rate of 2 °C min -1 , and finally the product V2O5 is obtained.

[0061] Comparative Example 2

[0062] The difference between Comparative Example 2 and Example 1 is that: during the process of adding the organic molecule malonamide (C3H6N2O2) in step (3), hydrochloric acid is not added and the pH is not adjusted. Other operations are the same as in Example 1.

[0063] Steps (1)-(2) are the same as in Example 1;

[0064] (3) 2.5 mmol of vanadium dioxide and 1 mmol of malonamide (C3H6N2O2) were dispersed in deionized water, and after vigorous stirring, the orange solution was transferred to a stainless steel autoclave lined with polytetrafluoroethylene, sealed and kept at 200°C for 6 hours. After the hydrothermal treatment, the autoclave was cooled to room temperature, washed with water and ethanol three times, and vacuum dried at 60°C.

[0065] (4) The dried material was further calcined in air at 350 °C for 2 h at a heating rate of 2 °C min -1 , and finally the product organic intercalated V2O5 is obtained.

[0066] Comparative Example 3

[0067] (1) 1 g of vanadium pentoxide was added to 30 mL of a 0.5 M sodium sulfate aqueous solution, stirred at room temperature for 72 h, washed with water and ethanol, and dried in vacuo to obtain the product sodium vanadate.

[0068] (2) 2.5 mmol of sodium vanadate and 1.2 mmol of malonamide (C3H6N2O2) were dispersed in deionized water, and the pH value was controlled at 5 by hydrochloric acid. After vigorous stirring, the solution was transferred to a stainless steel autoclave lined with polytetrafluoroethylene, sealed and kept at 200°C for 6 hours. After the hydrothermal treatment, the autoclave was cooled to room temperature, washed with water and ethanol three times, and vacuum dried at 60°C.

[0069] (3) The dried material was further calcined in air at 350 °C for 2 h at a heating rate of 2 °C min -1 , and finally the product of sodium vanadate organic intercalation is obtained.

[0070] The products obtained in the above examples and comparative examples are applied to positive electrode materials of batteries, as follows:

[0071] (1) Preparation of electrolyte:

[0072] Electrolyte for zinc ion storage: deionized water as solvent, zinc trifluoromethanesulfonate as zinc salt, 3 mol·L -1 The electrolyte is used for storage of zinc ions in zinc ion battery assembly.

[0073] (2) Preparation of positive electrode sheet:

[0074] The positive electrode active material organic molecular intercalation vanadium pentoxide, the conductive agent acetylene black, and the PVDF binder were mixed in a mass ratio of 7:2:1, ground evenly, added with N-methylpyrrolidone, and continued to stir evenly to obtain a slurry. The slurry was evenly coated on a stainless steel mesh and placed in a vacuum drying oven at 60°C for 10 hours.

[0075] (3) Preparation of batteries:

[0076] The positive electrode sheet, 3M Zn(OTF)2 aqueous electrolyte, sulfonated membrane, zinc sheet and gasket were assembled into a CR2016 button battery, the battery was sealed, and the electrochemical performance test was performed after standing for 2 hours. The experimental results of the above embodiments and comparative examples are as follows:

[0077] Figure 1The XRD patterns of two samples of malonamide intercalated vanadium pentoxide in Example 1 and non-intercalated vanadium pentoxide in Comparative Example 1 at a pH of about 5. It can be seen from the analysis of the figure that the sample after intercalation has a characteristic peak with small organic molecules at 8.6°, indicating that the organic molecules are successfully embedded in vanadium pentoxide. In addition, the (001) crystal plane of vanadium pentoxide has a significant red shift, indicating an increase in the interlayer spacing of the host material, which is conducive to the free shuttling of zinc ions.

[0078] Figure 2 The 200-nanometer SEM photos of two samples of malonamide intercalated vanadium pentoxide in Example 1 and non-intercalated vanadium pentoxide in Comparative Example 1 are shown. As can be seen from the figure, the precursor exhibits a dendritic structure with a large specific surface area. In addition, the two samples are not much different in size, both of which are nanorod structures of 1 micron in length and about 50 nanometers in width.

[0079] Figure 3 Example 1: 2 micron SEM photo of malonamide intercalated vanadium pentoxide. As can be seen from the figure, the intercalated vanadium pentoxide has the morphology of sea urchin-like aggregated nanospheres.

[0080] Figure 4 This is a TEM photo of the malonamide intercalated vanadium pentoxide sample of Example 1. As can be seen from the figure, the sample has a layered structure with an interlayer distance of 1.028 nanometers.

[0081] Figure 5 The zinc storage rate performance diagram of two samples of malonamide intercalated vanadium pentoxide in Example 1 and non-intercalated vanadium pentoxide in Comparative Example 1 is shown in Figure 1. The samples with the concentrations of 0.1, 0.5, 1, 3, 5, and 0.1 A g -1 The current density is used as the test condition. The battery capacity decreases with the increase of current density. -1 At the current density, the battery capacity is 319.6 mAh g -1 The second time, it returns to 0.1A g -1 The capacity did not change much, and the reversible capacity was still able to maintain at 517.3 mAh g -1 Unintercalated vanadium pentoxide in 5Ag -1 At the current density, the battery capacity is 203.14 mAh g -1 The second time, it returns to 0.1A g -1 The capacity decays significantly when the reversible capacity is 351.26 mAh g -1 Compared with unintercalated vanadium pentoxide, the battery tolerance of malonamide intercalated vanadium pentoxide is significantly enhanced.

[0082] Figure 6The figure shows the zinc storage cycle performance of two samples of malonamide intercalated vanadium pentoxide in Example 1 and non-intercalated vanadium pentoxide in Comparative Example 1. As can be seen from the figure, the cycle performance and reversible capacity of vanadium pentoxide after malonamide intercalation are significantly improved. -1 At the current density, after 500 cycles, the reversible capacity can be maintained at 405.4 mAh g -1 The capacity retention rate is about 98.2%, which is significantly higher than that of the non-intercalated vanadium pentoxide sample.

[0083] Figure 7 The XRD spectra of two samples of malonamide intercalated vanadium pentoxide prepared without adding hydrochloric acid in comparative example 2 and non-intercalated vanadium pentoxide in comparative example 1 are shown in Figure 1. As can be seen from the figure, the interlayer spacing of the sample intercalated with malonamide without adding hydrochloric acid is larger, and the interlayer spacing of the non-intercalated sample is smaller, but some miscellaneous peaks appear in the intercalated sample without adding hydrochloric acid.

[0084] Figure 8 This is a 500 nm SEM photograph of the malonamide intercalated vanadium pentoxide sample prepared without adding acid in Comparative Example 2. As can be seen from the figure, the morphology is not much different from that of the sample prepared under acidic conditions.

[0085] Fig. 9 The figure is a performance diagram of zinc storage rate of malonamide intercalated vanadium pentoxide prepared without adding acid in comparative example 2. As can be seen from the figure, compared with malonamide intercalated vanadium pentoxide in Example 1, the malonamide intercalated vanadium pentoxide prepared without adding acid has a higher zinc storage rate at 5·A g -1 At this current density, the reversible capacity is 203.14 mAh g -1 , back to 0.1Ag again -1 The current density and specific capacity are slightly reduced.

[0086] Fig.10 This is the zinc storage cycle performance diagram of the malonamide intercalated vanadium pentoxide sample prepared in comparative example 2 without adding acid. -1 At the current density, after 500 cycles, the reversible capacity can be maintained at 350 mAh g -1 It is about 2.34 nm, which is significantly lower than the sample with hydrochloric acid intercalated vanadium pentoxide in Example 1.

[0087] Fig.11 This is a graph showing the zinc storage cycle performance of the malonamide intercalated vanadium pentoxide sample prepared in Example 2 under the condition of a vanadium oxalate concentration of 0.166 M. As can be seen from the figure, at 0.5 Ag -1 At the current density, after 500 cycles, the reversible capacity is 251.7 mAh g -1 Around 50 Hz, the battery capacity decayed significantly, with a retention rate of 69.5%.

[0088] Fig.12 This is a graph showing the zinc storage cycle performance of the malonamide intercalated vanadium pentoxide sample prepared in Example 3 under the condition that the molar ratio of vanadium oxide precursor to malonamide is 3:1. As can be seen from the figure, at 0.5 A·g -1 At the current density, after 500 cycles, the reversible capacity is 407.2 mAh g -1 Around 100 Hz, the battery capacity decayed significantly, with a retention rate of 92.4%.

[0089] Fig.13 This is a graph showing the zinc storage cycle performance of the malononitrile intercalated vanadium pentoxide sample prepared in Example 4 at a pH of 5. As can be seen from the figure, at 0.5 A·g -1 At the current density, after 500 cycles, the reversible capacity is 300 mAh g -1 Around 100 Hz, the battery capacity decayed significantly, with a retention rate of 81%.

[0090] Fig.14 This is the zinc storage cycle performance diagram of the malonamide intercalated sodium vanadate sample of comparative example 3. As can be seen from the figure, at 0.5Ag -1 At the current density, after 500 cycles, the reversible capacity is 140.2 mAh g -1 Around 100 Hz, the battery capacity decayed significantly, with a retention rate of 89%.

[0091] Fig.15 This is the zinc storage cycle performance diagram of the malonamide intercalated vanadium pentoxide sample prepared under hydrothermal conditions for 24 h in Example 5. As can be seen from the figure, at 0.5 A g -1 At the current density, after 500 cycles, the reversible capacity is 291.8 mAh g -1 , the battery capacity is very unstable, and the battery structure is obviously damaged after 400 cycles. We infer that the main material structure is destroyed due to the long heating time, resulting in unstable coulombic efficiency.

[0092] The results show that the performance of the battery is greatly affected by changing the concentration of the vanadium oxalate solution, the heating time, the selected organic intercalation material and the inorganic vanadium source, etc. Among them, the performance of Example 1 is the most outstanding compared with other comparative examples, and it is selected as the final preparation method.

Claims

1. A method for preparing a composite positive electrode material of organic molecules embedded in a three-dimensional microstructure of vanadium pentoxide, characterized in that: (1) adding an organic small molecule to a vanadium oxide precursor dispersion to control the pH of the solution to be between 1 and 5; wherein the organic small molecule is selected from malonamide or malononitrile; (2) The solution is transferred to a high-pressure reactor, which is sealed for hydrothermal reaction. After the hydrothermal reaction, the solution is cooled to room temperature, the precipitate is collected by filtration, washed, dried, and calcined to obtain a composite positive electrode material in which organic molecules are embedded in a three-dimensional microstructure of vanadium pentoxide.

2. The method for preparing the composite positive electrode material of organic molecules embedded in a three-dimensional microstructure of vanadium pentoxide according to claim 1, characterized in that: The molar ratio of the vanadium oxide precursor to the organic small molecule is 1-3:0.5-1.5; the organic small molecule is malonamide.

3. The method for preparing the composite positive electrode material of organic molecules embedded in a three-dimensional microstructure of vanadium pentoxide according to claim 1, characterized in that: The hydrothermal reaction conditions of step (2) are 200° C. for 0.5 to 24 h.

4. The method for preparing the composite positive electrode material of organic molecules embedded in a three-dimensional microstructure of vanadium pentoxide according to claim 1, characterized in that: The preparation method of vanadium oxide precursor is as follows: (a) dissolving an inorganic vanadium source compound and oxalic acid in deionized water at a molar ratio, and vigorously stirring to form a VOC2O4 solution, wherein the concentration of the VOC2O4 solution is 0.66-0.165 M; (b) adding the VOC2O4 solution into a reaction kettle, slowly dropping hydrogen peroxide and anhydrous ethanol under stirring, stirring and mixing, heating to react, naturally cooling, collecting the precipitate by centrifugation, washing and drying to obtain a vanadium oxide precursor.

5. The method for preparing the composite positive electrode material of organic molecules embedded in a three-dimensional microstructure of vanadium pentoxide according to claim 4, characterized in that: The molar ratio of the inorganic vanadium source compound to oxalic acid is 1:

3.

6. The method for preparing the composite positive electrode material of organic molecules embedded in a three-dimensional microstructure of vanadium pentoxide according to claim 4, characterized in that: The inorganic vanadium source compound is selected from at least one of vanadium pentoxide, ammonium vanadate, vanadyl oxalate, vanadyl phosphate and vanadate.

7. The method for preparing the composite positive electrode material of organic molecules embedded in a three-dimensional microstructure of vanadium pentoxide according to claim 6, characterized in that: The inorganic vanadium source compound is selected from vanadium pentoxide.

8. The method for preparing the composite positive electrode material of organic molecules embedded in a three-dimensional microstructure of vanadium pentoxide according to claim 4, characterized in that: The heating reaction is carried out at 160 to 180° C. for 7 to 9 hours.

9. A composite positive electrode material of vanadium pentoxide embedded in a three-dimensional microstructure of organic molecules prepared by the method according to any one of claims 1 to 8.

10. Use of a composite positive electrode material of organic molecules embedded in a three-dimensional microstructured vanadium pentoxide prepared by the method according to any one of claims 1 to 8 in an aqueous zinc ion battery.

Citation Information

Cited By

  • Bimetal ion co-intercalation vanadium-based oxide as well as preparation method and application thereof

    CN121872439A